2021
DOI: 10.1088/1742-6596/2053/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Passive design of buildings: A review of configuration features for natural ventilation and daylighting

Abstract: Passive design involves the utilization of natural forces such as natural ventilation and daylighting without mechanical input of energy, and is a subset of environmentally sustainable design (ESD), which offers solutions for more environmentally friendly buildings. This review is based on the premise that ESD interventions have an inherent cost on building projects. The aim is to review existing research on applications of various building configurations for facilitating the economical application of passive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Table 4 summarises the fieldwork research findings and is based on a study, and it can be deduced that buildings with atriums have better indoor and outdoor air quality than buildings with light wells (Loo et al, 2021;. This fieldwork has found that PM10 levels in PPR2 are generally moderate-high, while PM10 levels in PPR1 are moderate-low.…”
Section: Discussionmentioning
confidence: 93%
“…Table 4 summarises the fieldwork research findings and is based on a study, and it can be deduced that buildings with atriums have better indoor and outdoor air quality than buildings with light wells (Loo et al, 2021;. This fieldwork has found that PM10 levels in PPR2 are generally moderate-high, while PM10 levels in PPR1 are moderate-low.…”
Section: Discussionmentioning
confidence: 93%
“…Passive design involves natural ventilation and daylighting without mechanical energy and can result in more environmentally friendly structures [5]. Because passive design minimises or limits solar heat gain and optimises natural ventilation and other heat and temperature-related issues, passive design is indirectly connected to thermal performance.…”
Section: Passive Designmentioning
confidence: 99%